What are aesthetic critical legal approaches trying to get us to understand about law? - Slomianski, David – (Kent Law Review, 2017)
In Horace’s Ars Poetica, the phrase ‘as painting, so poetry’ [ut pictura poesis] presupposes an equivalent aesthetic freedom between both poet and painter. Albeit with a different objective, Critical Legal Studies (CLS) aim at a similar outcome to Horace’s attempt; in relation to law—a connection between the individual and juridical rules—an intellectual evaluation or critique anent to a subjective perception that unifies law and aesthetics. With the groundwork provided by post-modernists largely empathetic to the Marxist and, in some cases, anarchistic cause, CLS scholars maintain an oft-repeated interpretation of classical as well as modern texts in view of notions apposite to social inequality or state oppression. Yet, by and large, the deep thought cascade extends to themes within the Frankfurt School, feminism, queer theory, legal realism (more pertinent to US’ CLS), amongst other approaches. The bulk of this paper will aim at a clear-cut inquiry into the intersections between the aforementioned CLS approaches, aesthetics and law.